News : . PTTI news
Since (1997):no.10 titled: News / Communications International. CONTINUED BY: UNInfo (ZK 52844). French ed.: (ZK 32185), (ZO 40428). - Spanish ed. (ZK 32169), (ZO 40424). - Norwegian ed.: (ZK 32209), (ZO 40496).